Consumers’ preferences on the use of eco-friendly bags: a green marketing perspective - Jonathan Camana Gano-an (Journal of Economics, Business, and Accountancy Ventura, 2017)
There has been a radical shift in consumer behavior towards a green lifestyle. Environmentalists were involved in massive green marketing campaigns trying to reduce the impact of plastic products to the environment. However, the problem is prevalent and evolved continuously. This paper furnishes a vital overview on the current environmental issues caused by plastic bags being used by hypermarkets and supermarkets. Consumer preferences and their perceptions on the use of eco bags were the highlights of this research. A total of 230 respondents were surveyed who are the local consumers in the City of Tagum. A quantitative research design was used in this paper. The study revealed that consumers have the highest perception on the use of Eco Bags in terms of environmental benefits. High level of consumer awareness about Eco Friendly bags as part of the green marketing campaign was found out. Further, research showed that consumers have no doubts of accepting the new marketing campaign as public acceptance exhibited a result of high level. The green marketing efforts of businesses generates substantive insights from the perspective of the consumers, as such, it is imperative that these efforts be intensively carried out and endlessly promote the green marketing efforts as the consumers affirmed their support by putting a greener value to it.